Energy harvesting from pneumatic secondary suspensions for vehicle monitoring. Issue 1 (September 2020) - Genovese, A; D'Angelo, G A; Strano, S; Terzo, M
Abstract: In this paper, an activity concerning the design and the development of a vibration-based energy harvesting system is described. It consists of a piezoelectric based resonant device integrated in an air spring. A simulation study, together with the first experimental tests, have been carried out. The activity shows the goodness of the proposed solution as new concept of self-powered monitoring systems.